Calculation ferroelectric hysteresis loop via an explicit function. Issue 1 (4th May 2017) - Changshi, Liu
ABSTRACT: In this paper, a very simple methodology to characterize the polarization of ferroelectrics via electrical field is proposed. This methodology allows us to use not only experimental electrical field-polarization curve as classical models do, but also physical status of ferroelectrics. The methodology is based on the use of Fermi-Dirac distribution, from eight measured P–E curves of two ferroelectrics materials, the theoretical polarization-electrical field curve repeat experimental path very well. Meanwhile, the effects of physical status on ferroelectric hysteresis loop are explained through mathematical route.